2022
DOI: 10.3389/fimmu.2022.833254
|View full text |Cite
|
Sign up to set email alerts
|

Tear miRNAs Identified in a Murine Model of Sjögren’s Syndrome as Potential Diagnostic Biomarkers and Indicators of Disease Mechanism

Abstract: ObjectiveThe tear miRNAome of the male NOD mouse, a model of ocular symptoms of Sjögren’s syndrome (SS), was analyzed to identify unique miRNAs.MethodsMale NOD mice, aged 12-14 weeks, were used to identify tear miRNAs associated with development of autoimmune dacryoadenitis. Age- and sex-matched male BALB/c mice served as healthy controls while age-matched female NOD mice that do not develop the autoimmune dacryoadenitis characteristic of SS were used as additional controls. Total RNA was isolated from stimula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Sjögren’s syndrome (SS), first described in 1933 [ 1 ], is an autoimmune disease mediated by the infiltration of lymphocytes into the exocrine glands, including the salivary and lacrimal glands [ 2 , 3 ]. Lymphocyte infiltration leads to destruction of glandular tissue and dysfunctional glandular secretion, followed by dry eyes and mouth [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sjögren’s syndrome (SS), first described in 1933 [ 1 ], is an autoimmune disease mediated by the infiltration of lymphocytes into the exocrine glands, including the salivary and lacrimal glands [ 2 , 3 ]. Lymphocyte infiltration leads to destruction of glandular tissue and dysfunctional glandular secretion, followed by dry eyes and mouth [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wei Cong et al suggested that mmu‐miR‐30e‐3p were also differentially expressed in liver tissue from rats with acute Toxoplasma gondii infection, 26 however, mmu‐miR‐30e‐3p targeting IL‐1rn regulates the inflammatory response caused by parasitic infections and no studies have been reported. Hu et al found that miR‐203‐3p may bind to vascular endothelial growth factor A (Vegfa) and participate in snhg8‐mediated apoptosis and angiogenesis in AML cells 27 . Moreover, mmu‐miR‐203‐3p was identified as a potential diagnostic biomarker and indicator of Sjögren's syndrome 28 .…”
Section: Discussionmentioning
confidence: 99%
“…miR-17-92 (rs4284505) [113], miR-146a [114], miR-365a-3p [115], miR-4689 [116] miR-21 [117], miR-124-3p, miR-146, miR-320b, miR-377-3p [118,119] miR-181a, miR-223 [120], miR-485-5p [121] miR-7 [122], miR-30a [123], miR-181d-5p [124], miR-590-3p [125] Antiphospholipid syndrome miR-326, miR-483-3p [126] miR-19b-3p, miR-20a-5p [127] miR-146a-5p [128] Systemic sclerosis, scleroderma miR-21 [129], miR-126 [130], miR-155-5p [131] miR-21 [132], miR-27a [133], miR-29a, miR-138 [134] miR-21-5p, miR-29a-3p, miR-143, miR-155 [135], miR-181b-5p, miR-210-3p, miR-223-3p [136] miR-27a [137], miR-214 [138] Sjögren's syndrome miR-181d-5p [139], miR-223-3p [140] miR-30 [141], miR-181b-5p, miR-322-5p, miR-424-5p, miR-503-5p [142], miR-513c-3p [143], miR-1290, let-7b-5p [144] miR-92a [145] miR-16, miR-125b [146], miR-142, miR-223 [147], let-7 [148] Autoimmune vasculitis miR-424-5p [149] miR-24-3p [150], miR-30a-5p, miR-33, miR-34 [151], miR-99a-5p, miR-106b-5p, miR-133a [152], miR-146a-5p [149], miR-148b-3p, miR-155-5p, miR-182-5p…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Combined evaluation of exosome-derived miR-1290 and let-7b-5p in mouth-rinse samples distinguished patients with Sjögren's syndrome from healthy volunteers with 91.7% sensitivity and 83.3% specificity [144]. According to results obtained from a murine model of Sjögren's syndrome, miR-181b-5p, miR-322-5p and miR-503-5p may be applied as novel biomarkers of autoimmune dacryoadenitis [142]. In minor salivary gland tissue samples of patients with primary Sjögren's syndrome, the expression level of miR-92a inversely correlated with disease severity [145].…”
Section: Sjögren's Syndromementioning
confidence: 99%